2018
DOI: 10.1016/j.radcr.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pineal gliosarcoma in a 5-year-old girl

Abstract: The purpose of this paper is to report a rare case of a pediatric pineal gliosarcoma. Gliomas on the pineal region are uncommon, representing 0.4%-1% of all brain tumors. Furthermore, pediatric gliosarcomas are a very rare entity. We present a case of a 5-year-old girl, with a history of headache, vomiting, diplopia, and gait disturbances. A pineal tumor was found with pathology results consistent with a gliosarcoma. A total of 25 cases of pediatric gliosarcomas have been reported, none of them in pineal topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A case of pediatric gliosarcoma associated with NF1 was recently reported by Dogan et al [33]. Granados et al reported a pineal gliosarcoma in a five-year-old girl, the first reported case in this unusual location [29]. Various studies have emphasized the importance of gross total resection in achieving relatively better prognosis [23,32].…”
Section: Discussionmentioning
confidence: 99%
“…A case of pediatric gliosarcoma associated with NF1 was recently reported by Dogan et al [33]. Granados et al reported a pineal gliosarcoma in a five-year-old girl, the first reported case in this unusual location [29]. Various studies have emphasized the importance of gross total resection in achieving relatively better prognosis [23,32].…”
Section: Discussionmentioning
confidence: 99%
“…The PG has been described as a small, odd, endocrine organ located in the roof of the midbrain, above the superior colliculi and behind the third ventricle (16). It is joined to the habenular and posterior commissures by means of the pineal stalk, whose body is bathed by cerebrospinal fluid and covered by pia mater, the pia mater in turn becomes a capsule that provides the gland with partitions that in turn allow its irrigation (17).…”
Section: Morphological Structurementioning
confidence: 99%
“…On the other hand, its irrigation, unlike others in the body, is considered of a high flow considering that it is a small organ, in addition to the fact that the blood vessels that integrate it lack a blood-brain barrier (13,16). In addition, a study by Macchi & Bruce identified that the PG reached a blood flow that equaled the neurohypophysis in rats and was exceeded only by the flow from the kidneys (12,13).…”
Section: Morphological Structurementioning
confidence: 99%